2013
DOI: 10.4021/jmc1223w
|View full text |Cite
|
Sign up to set email alerts
|

Signet Ring Cell Carcinoma of the Duodenal Bulb With Metastases to the Ovaries and the Colon: A Case Report

Abstract: Primary duodenal cancer is a rare entity which has accounted for only 0.3% of all gastrointestinal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…8 Henry et al reported a case of signet ring cell carcinoma of duodenal bulb with metastasis to ovaries and colon. 9 None of these reports showed a radical resection with curative intent and long-term follow up and survival. Therefore, this is a rare case scenario in which highly aggressive duodenal carcinoma with isolated ovarian metastasis in good performance status patient, radical surgery is still feasible and can be offered if possible.…”
Section: Discussionmentioning
confidence: 99%
“…8 Henry et al reported a case of signet ring cell carcinoma of duodenal bulb with metastasis to ovaries and colon. 9 None of these reports showed a radical resection with curative intent and long-term follow up and survival. Therefore, this is a rare case scenario in which highly aggressive duodenal carcinoma with isolated ovarian metastasis in good performance status patient, radical surgery is still feasible and can be offered if possible.…”
Section: Discussionmentioning
confidence: 99%
“…We also found 1 report where SRCC of the duodenum spread to the ovaries, peritoneum, and colon, and on endoscopy, there was an exophytic obstructing duodenal bulb mass. 14 SRCC is a unique histologic subtype of CRC and is defined as a poorly cohesive carcinoma 15 where greater than 50% of tumor cells show abundant cytoplasm mucin and eccentric crescentshaped nuclei. 16 SRCC in the distal gastrointestinal tract comprises 1% of all cases of colon cancer and 15.3% of all SRCC cases.…”
Section: Discussionmentioning
confidence: 99%
“…We also found 1 report where SRCC of the duodenum spread to the ovaries, peritoneum, and colon, and on endoscopy, there was an exophytic obstructing duodenal bulb mass. 14 …”
Section: Discussionmentioning
confidence: 99%